Religiosity as a Stress Buffer: An Investigation of Muslim Women's Work-Life Conflict and Job Stress among Minangkabau Women - Purbo Jadmiko; Elfitra Azliyanti; Muhammad Rizky Prima Sakti (Universitas Muhammadiyah Yogyakarta, 2023)
This study investigates the impact of work-life conflict on work stress among Minangkabau women in diverse organizational settings. Data from 179 respondents were collected through purposive sampling using a survey approach. The research instrument incorporated variables such as perceived social support, work-life conflict, religiosity, and work stress. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were employed for data analysis. Results indicate a significant influence of work-life conflict and religiosity on work stress levels, underscoring its pivotal role in shaping employees' psychological well-being. However, hypotheses concerning perceived social support (PSS) were not supported, revealing the intricacy of these relationships. Hypothesis testing demonstrated a notable relationship between work-life conflict and work stress, while perceived social support exhibited no significant impact. The discussion highlights the imperative of managing work-life conflict for stress reduction. The complex interplay among religiosity, perceived social support, and stress levels, moderated by contextual factors, was acknowledged. Recommendations include further research on religiosity and stress, exploring factors influencing PSS, and an in-depth analysis of social support dynamics. In conclusion, this study enhances our comprehension of nuanced relationships impacting work stress, providing insights for future interventions and managerial strategies to foster a supportive work environment.